INTEGRASI HASIL RISET DALAM PENGAYAAN BAHAN AJAR MGMP EKONOMI SMA DI KOTA PALU - Patta Tope; Mohamad Ichwan; Muh Ichsan; Santi Yunus; Novita Sari (JOURNAL OF COMMUNITY DEDICATION, 2026)
Improving the quality of student learning is key to achieving Indonesia Emas 2045, which includes improving teacher competence, relevant curricula, educational infrastructure, and the use of technology, as well as strengthening character values. One way to improve the quality of learning is by improving the quality of teaching materials used in student learning activities. Therefore, enriching teaching materials is very important in developing teaching materials for educators and students. Interesting and relevant teaching materials are very important to support the success of the learning process. Through Community Service activities, the team will conduct a series of sharing sessions on research results from universities related to topics relevant to Economics teaching materials at the senior high school level, in order to integrate research results with Economics teaching materials in senior high schools. They will also hold discussions and sharing sessions related to obstacles in developing teaching materials and in learning activities. The stages to be implemented are the preparation stage, the implementation stage, and the evaluation stage. This activity will produce documentation in electronic media. The targets to be achieved are the integration of university research results into teaching materials to improve the quality of learning for senior high school students, enabling educators to develop more effective and efficient teaching materials, and creating a more interesting and interactive learning process, as well as the implementation of community service activities with the output in the form of documentation of Community Service Activities in 2025.